Pemberdayaan Gelandangan dan Pengemis Melalui Teknologi Informasi. - Yati, Nurhayati; Sembiring, Terang Muly; Simatupang, Baharis Setia Adisahputra; Arisman; Syahrial Sitorus; Barus, Apriwati (Jurnal Masyarakat Indonesia (Jumas), 2025)
Homelessness and beggars are social problems that are often found in various regions of Indonesia, especially Binjai City. This causes fewer job opportunities, inadequate human resources and increases people’s living need. To overcome this problem, Dinas Sosial Kota Binjai created a policy to deal with homeless people and beggars by providing basic information technology training. This Community servis aims to empower homeless people and beggars to improve skills, access information and work opportunities for disadvantaged community groups. By providing skills to teach how to access relevant information such as health service, social assistance, free education and job vacancies.